Empowering Junior High School Students in Jambi Through Legal Counseling on Sexual Violence Prevention - Amir , Latifah; Budhiartie, Arrie; Amir, Diana; Dewi, Ratna; Suci Pratiwi, Cholillah (Jurnal Karya Abdi Masyarakat, 2024)
Concerns about the increasing prevalence of deviant behavior related to sexual activities and sexual harassment, where teenagers often become victims, must be addressed intensively by all sectors, including academia. This concern serves as a strong motivation for the Community Service Team from the Faculty of Law to focus on the prevention and mitigation of sexual violence among adolescents, specifically at Secondary School Number 6 Kota Jambi. The selection of this location is based on the understanding that junior high school students are a vulnerable group, susceptible to becoming victims due to their emotional instability and heightened curiosity. Preventive efforts are implemented by providing students with better knowledge and understanding, enabling them to protect themselves and their peers while fostering awareness of anti-sexual violence in their environment. The outreach method involves several stages, including preliminary assessments, problem identification, and the socialization of various regulations related to antisexual violence. Socialization activities are conducted through presentations and discussions between the team and the students. The final stage includes periodic evaluations conducted by the school to assess the development of students' knowledge and behavior regarding sexual violence and harassment. In conclusion, this research conveys a message about the importance of higher education institutions in supporting students to understand legal issues related to sexualviolence that frequently occur today.